1985
DOI: 10.1002/aja.1001720306
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic histology of the antral epithelilum in the mouse stomach: IV. Ultrastructure and renewal of gland cells

Abstract: The renewal of gland cells was investigated by three-dimensional reconstruction of typical mucous units of the pyloric antrum using electron microscopy and 3H-thymidine radioautography in 3 to 4 month-old CD1 mice. Based on analysis of 42 units, the average gland measured 31 micron in length and was composed of 37 (mucous) gland cells with eight enteroendocrine cells scattered among them. The gland neck cells located close to the isthmus showed the cytoplasmic and nuclear features characteristic of differentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
43
0
1

Year Published

1985
1985
2003
2003

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 79 publications
(46 citation statements)
references
References 13 publications
2
43
0
1
Order By: Relevance
“…It is noteworthy that Msi-1 expression is also expressed in the mammalian intestine (Sakakibara et al, 1996), where putative stem cells and at least the next two generations are positive for Msi-1 (Potten et al, 2003). Although Msi-1 expression became hardly detectable towards the end of metamorphosis, possibly due to a low immunoreactive sensitivity in this study, Msi-1 expression could be detectable in the region where proliferating cells were localized in both the intestine and the stomach, that is, in the trough of intestinal folds corresponding to the mammalian crypt (Cheng and Bjerknes, 1985;Potten et al, 1997) or in the neck region of gastric glands similar to that of mammalian glands (Lee and Leblond, 1985). These results indicate that the adult progenitor cells during amphibian metamorphosis include stem cells analogous to the mammalian ones, and molecular mechanisms underlying the control of these stem cells are conserved across the amphibian and mammalian gastrointestines.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…It is noteworthy that Msi-1 expression is also expressed in the mammalian intestine (Sakakibara et al, 1996), where putative stem cells and at least the next two generations are positive for Msi-1 (Potten et al, 2003). Although Msi-1 expression became hardly detectable towards the end of metamorphosis, possibly due to a low immunoreactive sensitivity in this study, Msi-1 expression could be detectable in the region where proliferating cells were localized in both the intestine and the stomach, that is, in the trough of intestinal folds corresponding to the mammalian crypt (Cheng and Bjerknes, 1985;Potten et al, 1997) or in the neck region of gastric glands similar to that of mammalian glands (Lee and Leblond, 1985). These results indicate that the adult progenitor cells during amphibian metamorphosis include stem cells analogous to the mammalian ones, and molecular mechanisms underlying the control of these stem cells are conserved across the amphibian and mammalian gastrointestines.…”
Section: Discussionmentioning
confidence: 79%
“…Meanwhile, in the stomach, the adult epithelium acquires the cell renewal system where proliferating cells are localized in the neck region of glands (Oinuma et al, 1992) similar to that of the mammalian gastric glands (Lee and Leblond, 1985;Nomura et al, 1998), and finally differentiates into the surface mucous epithelium and the glandular epithelium, which consists of major glandular cells expressing pepsinogen (Pg) (Inokuchi et al, 1995;Ishizuya-Oka et al, 1998), mucous neck cells, and endocrine cells (Holmberg et al, 2001). Therefore, it is suggested that progenitor cells of the adult epithelium that appear as undifferentiated cells during metamorphosis in these organs include multipotent stem cells analogous to those in the mammalian gastrointestine.…”
mentioning
confidence: 99%
“…Parietal, enteroendocrine, and caveolated cells migrate in both directions (15,17,20,(22)(23)(24)(25)29). In the antrum, units are similarly organized but consist mostly of mucous cells, although parietal and enteroendocrine cells are also found in some antrum units (18,27,30).…”
mentioning
confidence: 88%
“…Some of the granulefree cells located in the isthmus are proposed to act as multipotential stem cells giving rise to prepit, preparietal, and preneck cells, which then act as progenitors committed to their respective cell lineages (22,25,30). However, there is no direct evidence in the adult stomach for multipotential stem cells.…”
mentioning
confidence: 95%
“…The latter is the largest part of the gland and contains chief cells, parietal cells and sporadic mucous cells. Isolated endocrine cells can be found in all glandular tracts (Lee and Leblond, 1985). Among the molecular signals that regulate the activity of gastric cells, Fig.…”
Section: Discussionmentioning
confidence: 99%